Continuous local anaesthetic wound infusion in infants undergoing thoracic or abdominal surgery: A systematic review - Jeewan Jyoti; Eva Sloukova; Kaye Spence; Annabel Webb; Albert Shun; Himanshu Popat (Elsevier, 2024)
Objective: To determine whether continuous local anaesthetic wound infusion (CLAWI) provides more effective pain relief and decrease the need for systemic opioids compared to other analgesic agents in term or preterm newborn infants undergoing thoracic or abdominal surgery. Methods: Cochrane Central Register of Controlled Trials, Medline, Embase and CINAHL were searched from database inception to August 2022. Publications were screened and their references were hand-searched to identify additional studies. This review included randomized controlled trials (RCTs), quasi-RCTs, and cluster RCTs. Two reviewers independently extracted data and examined the methodological quality of the eligible studies. A meta-analysis was performed for available outcomes. Results: After screening 1202 articles, two RCTs with 98 patients were included. Meta-analysis for combined data was possible for only two outcomes: pain scores post-surgery and length of hospital stay. The random effects model for the pooled standardised mean difference of pain scores between treatment groups post-surgery was -2.54 (95 % CI:7.53, 2.46, p = 0.3196) and for length of stay in the NICU was -0.19 (95 % CI:0.58, 0.21, p = 0.3574), suggesting that CLAWI was not more effective in either providing pain relief or reducing length of stay. However, the small number of studies included, the considerable heterogeneity between the studies, and the small sample sizes of the individual studies limit the generalizability of the findings. Conclusion: This review highlights the need for further, adequately powered well-designed, multicentre trials to examine the effectiveness of CLAWI in reducing postoperative pain in newborns undergoing abdominal and thoracic surgery. Level of evidence: Level I - Evidence from a systematic review of all relevant randomized controlled trials